Handgrip automotive prototype of polypropylene reinforced benzoyl treated kenaf and sugar palm fibers: a facile flexural strength and hardness studies - Shaharuddin, Mohd Izwan; Salit, Mohd Sapuan; Mohamed Yusoff, Mohd Zuhri; Abdul Rahman, Mohamed (King Mongkut University of Technology North Bangkok, 2022)
Combining two or more different types of fibers within a polymer matrix is defined as hybrid composites. The requirements for an impressive hybrid composites include compatible weight ratio, good compressive strength, low-cost production and ease of fabrication. Moreover, hybrid composites provide a combination of remarkable mechanical properties including tensile modulus, compression, impact strength, flexural and hardness, which are comparable with the metal-based product materials. Recently, hybrid composites have been established due to their remarkable performance and efficiency. This study presents a facile analysis of polypropylene (PP) reinforced benzoyl treated kenaf and sugar palm fibers for handgrip prototype application. The materials were further analyzed for their materials molding modeling, and facile mechanical behavior including flexural strength, flexural modulus, Rockwell hardness (HRF), and also weight reduction percentage test. Hybrid composite T-SP7K3 shows higher flexural strength and flexural modulus compared to the ABS (Perodua Axia) at 339.5 MPa and 17.19 MPa, respectively. In addition, the HRF testing shows a higher value of hybrid composite (at 92.96 N/mm2) compared with the ABS handgrip with. Furthermore, the weight reduction percentage also recorded hybrid composite T-SP7K3 with the highest value at 22.7%.